Ameloblastic Fibro-Odontoma: A Diagnostic Challenge - Elen de Souza Tolentino; Bruna Stuchi Centurion; Marta Cunha Lima; Patrícia Freitas-Faria; Alberto Consolaro; Eduardo Sant'ana (Hindawi Limited, 2010)
An 11-year-old girl presented to our department to have a second opinion regarding a lesion involving her left mandible. She had previously undergone several radiographic exams including panoramic, helical, and cone-beam computed tomography. Radiographic examinations revealed a well-defined radiolucent region, which contained an irregular radiopaque mass of 3 cm in diameter, localized to the left angle of the mandible. Our presumptive diagnosis was complex odontoma. Excisional biopsy was performed, and microscopic features showed strands and islands of odontogenic epithelium showing peripheral palisading and loosely arranged central cells, identical to stellate reticulum, embedded in a myxoid cell-rich stroma resembling the dental papilla. Dentin and enamel were also presented. The diagnosis was ameloblastic fibro-odontoma, which is a rare mixed odontogenic tumor, derived from epithelial and ectomesenchymal elements that form the dental tissues.